2021
DOI: 10.3390/e23070854
|View full text |Cite
|
Sign up to set email alerts
|

Improved Effort and Cost Estimation Model Using Artificial Neural Networks and Taguchi Method with Different Activation Functions

Abstract: Software estimation involves meeting a huge number of different requirements, such as resource allocation, cost estimation, effort estimation, time estimation, and the changing demands of software product customers. Numerous estimation models try to solve these problems. In our experiment, a clustering method of input values to mitigate the heterogeneous nature of selected projects was used. Additionally, homogeneity of the data was achieved with the fuzzification method, and we proposed two different activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The number of iterations required for a complete factorial analysis is N = L P (e.g., when three levels with The main advantages of this model are the relatively straightforward architecture of the presented construction of the artificial neural network ANN-L36, wide coverage of different projects, the minimal number of iterations, reduced execution time of iterations, and reliability of the obtained results. 40,41 Additional extensions to this model could be validation on different datasets and by the introduction of other criteria. There are no limitations in applying this model.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The number of iterations required for a complete factorial analysis is N = L P (e.g., when three levels with The main advantages of this model are the relatively straightforward architecture of the presented construction of the artificial neural network ANN-L36, wide coverage of different projects, the minimal number of iterations, reduced execution time of iterations, and reliability of the obtained results. 40,41 Additional extensions to this model could be validation on different datasets and by the introduction of other criteria. There are no limitations in applying this model.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Azzeh et al addressed the issue of determining the number of projects nearby using a method known as bisecting k-medoids [14]. It is shown in [15] that grouping of varied projects into clusters can aid in accurate evaluation. In this paper, it is confirmed that clustering improves estimate accuracy.…”
Section: Related Work -Other Approach For Dataset Segmentation (Data ...mentioning
confidence: 99%
“…Azzeh et al, addressed the issue of determining the number of nearby projects by using a method known as bisecting k-medoids [10]. It is demonstrated in [11] that grouping varied projects into clusters can aid to accurate assessment. In this paper is confirmed that clustering improves estimate accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…All experiments were evaluated using the following criteria [37][38][39]: mean absolute residual (MAR), calculated by using (7), mean magnitude of the relative error (MMRE), as in (8), percentage relative error deviation (PRED), as in (9), and mean absolute percentage error (MAPE), as in (10). Finally, the sum of squared errors (11) and mean squared error (MSE), as in (12), were included in the evaluation.…”
Section: Evaluation Criteriamentioning
confidence: 99%